PEMBUATAN HERBAL CENGKEH OLEH KELOMPOK MASYARAKAT DI DESA HALONG, KECAMATAN BAGUALA KOTA AMBON - Veince Benjamin Silahooy; Denny Latumaerissa (BAKIRA: Jurnal Pengabdian Kepada Masyarakat, 2020)
Clove leaves are a local Maluku plant that can increase the work of lymphocytes which function to protect the body from antigen attacks that can damage the body. Clove leaf extract has the potential to increase macrophage activity. Macrophages are one of the cells that play an important role in the immune response of living things so that the body will be able to withstand attacks from outside which can interfere with bodily functions. Community service is carried out to foster and train community groups in processing clove leaves into a salable herbal tea. The goal is to improve consumer health and support the economic needs of partners. So that economic and social problems that often arise in the social life of community service partner groups can be eliminated. The results obtained are that several economic and social problems from partners can be resolved, including the availability of equipment that can support production activities. In addition, partners who do not have a job indirectly have the opportunity to open employment opportunities which of course can bring benefits, and partner members' habit of consuming alcohol is also slowly decreasing.